GWAS for the identification of introgressed candidate genes of Sinapis alba with increased branching numbers in backcross lines of the allohexaploid Brassica - Singh, Kaushal Pratap; Kumari, Preetesh; Rai, Pramod Kumar (Frontiers in Plant Science, 2024)
Plant architecture is a crucial determinant of crop yield. The number of primary (PB) and secondary branches (SB) is particularly significant in shaping the architecture of Indian mustard. In this study, we analyzed a panel of 86 backcrossed introgression lines (BCILs) derived from the first stable allohexaploid Brassicas with 170 Sinapis alba genome-specific SSR markers to identify associated markers with higher PB and SB through association mapping. The structure analysis revealed three subpopulations, i.e., P1, P2, and P3, in the association panel containing a total of 11, 33, and 42 BCILs, respectively. We identified five novel SSR markers linked to higher PB and SB. Subsequently, we explored the 20 kb up-and downstream regions of these SSR markers to predict candidate genes for improved branching and annotated them through BLASTN. As a result, we predicted 47 complete genes within the 40 kb regions of all trait-linked markers, among which 35 were identified as candidate genes for higher PB and SB numbers in BCILs. These candidate genes were orthologous to ANT, RAMOSUS, RAX, MAX, MP, SEU, REV, etc., branching genes. The remaining 12 genes were annotated for additional roles using BLASTP with protein databases. This study identified five novel S. alba genome-specific SSR markers associated with increased PB and SB, as well as 35 candidate genes contributing to plant architecture through improved branching numbers. To the best of our knowledge, this is the first report of introgressive genes for higher branching numbers in B. juncea from S. alba.